探討高雄市青少年自覺健康、身體意象及幸福感之關係 Relationships Between the Self-Perceptions of Health Awareness, Body Image, and Well-Being Among Adolescents in Kaohsiung - 吳枚瑛 Mei-Ying Wu; 陳香廷 Hsiang-Ting Che; 魯盈讌 Ying-Yen Lu; 洪瑞兒 Zuway-R Hong (National Taiwan Normal University, 2018)
本橫斷調查研究目的在探討青少年於自覺健康、身體意象與幸福感的差異性及中介效果。本研究以分層叢集抽樣方式選取高雄市國中、高中及大學一年級共計1,129位學生為研究對象，以三種自編量表蒐集青少年自覺健康、身體意象與幸福感的現況。首先，以探索性及驗證性因素分析及內部一致性信度檢驗量表之信度與效度，再以描述性統計、獨立性t檢定、單因子變異數分析，比較不同背景的青少年在自覺健康、身體意象及幸福感的差異情形，最後，使 用結構方程模式檢驗青少年自覺健康、身體意象、幸福感間相關性與預測力。本研究發現，七年級學生的自覺健康與身體意象總分顯著高於高一及大一學生，男學生自覺健康與身體意象總分顯著高於女學生，而女學生的幸福感顯著高於男學生，青少年的身體意象對於自覺健康及幸福感具有顯著完全中介效果。本研究建議融入健康教育理論與實務於各級學校和各學科領域課程與教學及各類型活動中，以引導青少年樹立正確身體意象觀念及提升幸福感。 This survey investigated the relationships between the health awareness, body image, and well-being of Taiwanese adolescents. The mediation effects of students' health awareness on the relationship between their body image and well-being were explored. A total of 1,129 adolescents were selected through stratified random sampling from seven junior high schools (seventh-grade students), six senior high schools (tenth-grade students), and five universities in Kaohsiung (freshmen). Three well-structured scales-health awareness, body image, and well-being scales-were conducted to measure adolescents' health awareness, body image, and well-being. Subsequently, data from the measurements were compared by conducting individual t-tests, one-way analyses of variance, and structural equation modeling. The results revealed that the seventh-grade students possessed significantly higher scores on the health awareness and body image parameters compared with the tenth-grade students and freshmen. The adolescent boys possessed significantly higher total scores on the health awareness and body image parameters compared with the adolescent girls. The well-being total score of the adolescent girls was significantly higher than that of the adolescent boys. In addition, this study provides evidence to support the fact that adolescents' body image is a mediating factor between health awareness and well-being. This study adds empirical evidence and provides insights into how grade and gender differences can be integrated in planning and implementing effective pedagogical strategies for increasing adolescent' health awareness, body image, and well-being in Taiwan.